Government policy changes and organizational goal setting: Extensions to the behavioral theory of the firm - Shinkle, George A.; Hodgkinson, Gerard P.; Gary, Michael Shayne (Journal of business research, 2021)
The increasing frequency and extent of government policy changes in many countries and industries has exposed an important theoretical gap about how such changes influence organizational goal setting. This paper extends the behavioral theory of the firm to account for changes in government policy on goal dimensions (i.e., what goals are adopted) and goal aspirations (i.e., the target levels adopted). We advance propositions regarding the specification of goal dimensions and add a new factor into the aspiration adaptation model to account for anticipatory (i.e., forward-looking) responses on the part of firms to government policy changes.